An investigation of the teacher’s challenges and strategies in teaching English in a rural area - Zulaeha, Siti; Riyanti, Dwi (Yayasan Mitra Persada Nusantara, 2024)
The purpose of this study was to investigate the challenges faced by an English teacher and the strategies to solve the challenges in teaching English in a rural area, namely Sebangki. This narrative study used interview with an English teacher at SMA Negeri 1 Sebangki. The results of this study indicated that there are two main themes of challenges faced by teacher including the challenges from the teacher consists of distance to school, teaching other subjects, lack of teacher training, and students problems consists of lack of interest, lack of confidence, lack of vocabulary mastery and students’ attendance. To overcome those challenges, the English teacher employed some strategies including using media and strategy in teaching, giving motivation and even giving punishment to the students.